Analysis of Fiscal Factors for Disaster Risk Communities - Retno Yuli Hastuti; Edy Haryanto; Romadhani Romadhani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Klaten Regency is an earthquake prone area because its location is crossed by a plate and is included in the category of single hazard earthquake hazard which is ranked 2nd in the District in Indonesia. The area of Muruh Gantiwarno Village, Klaten is one of the sub-districts in Klaten that was most affected by the Jogja Earthquake on May 27, 2006. This research aims to find out what factors are influencing the disaster-prone preparedness of the Muruhidalwar Klaten village.This type of research uses descriptive analytic with cross sectional approach. The sampling technique is proportional stratified random sampling. The sample used was 119 respondents from 3 Kadus. Statistical tests use simple logistic regression and multiple logistic regression. The results obtained by factors that influence preparedness include knowledge (p value 0.001), attitude (p value 0.013), policies and guidelines (0.246), plans for disaster emergency response (p value 0.113), disaster simulation (p value 0.007) and ability to mobilize resources ( p value 0.036). The conclusion of this study was that the factors that most influence disaster prone community preparedness are knowledge with the results of p value 0.015 (α; 0.05) and OR (odds ratio) 3.101, which means that it influences as much as 3,101 times against disaster preparedness.